3K3A-Activated Protein C Protects the Blood-Brain Barrier and Neurons From Accelerated Ischemic Injury Caused by Pericyte Deficiency in Mice - Wang, Yaoming; Kisler, Kassandra; Nikolakopoulou, Angeliki Maria; Fernandez, Jose A.; Griffin, John H.; Zlokovic, Berislav V. (Frontiers in Neuroscience, 2022)
Pericytes, mural cells of brain capillaries, maintain blood-brain barrier (BBB), regulate cerebral blood flow (CBF), and protect neurons against ischemic damage. To further investigate the role of pericytes in ischemia, we induced stroke by 45 min transient middle cerebral artery occlusion (tMCAo) in 6-month-old pericyte-deficient Pdgfrb+/- mice and control Pdgfrb+/+ littermates. Compared to controls, Pdgfrb+/- mice showed a 26% greater loss of CBF during early reperfusion, and 40-50% increase in the infarct and edema volumes and motor neurological score 24 h after tMCAo. These changes were accompanied by 50% increase in both immunoglobulin G and fibrinogen pericapillary deposits in the ischemic cortex 8 h after tMCAo indicating an accelerated BBB breakdown, and 35% and 55% greater losses of pericyte coverage and number of degenerating neurons 24 h after tMCAo, respectively. Treatment of Pdgfrb+/- mice with 3K3A-activated protein C (APC), a cell-signaling analog of plasma protease APC, administered intravenously 10 min and 4 h after tMCAo normalized CBF during the early reperfusion phase and reduced infarct and edema volume and motor neurological score by 55-60%, with similar reductions in BBB breakdown and number of degenerating neurons. Our data suggest that pericyte deficiency results in greater brain injury, BBB breakdown and neuronal degeneration in stroked mice and that 3K3A-APC protects the brain from accelerated injury caused by pericyte deficiency. These findings may have implications for treatment of ischemic brain injury in neurological conditions associated with pericyte loss such as those seen during normal aging and in neurodegenerative disorders such as Alzheimer’s disease.